FACTORS AFFECTING PROFITABILITY WITH THE INTEREST RATE AS MODERATING VARIABLES IN BANK SUMUT - Andhikatama, Andhikatama (Asosiasi Dosen Akuntansi Indonesia, 2020)
The purpose of this study is to examine the effect of the Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Operational efficiency (BOPO), Net Interest Margin (NIM), and Current Account Saving Account (CASA) partially and simultaneously to PT. Bank Sumut profitability with Bank Indonesia (BI) Rates as a moderating variable. The population of this research is the branch office of PT. Bank Sumut which has been established during the observation period from 2014 to 2018. This study uses purposive sampling. The analytical tool used is panel data regression and data processing using software Stata 13. The results of this test show that the NPL and LDR ratios have a negative effect on ROA, while the BOPO, NIM, and CASA ratios have a positive effect on ROA. BI Rates cannot moderate the relationship between the ratio of NPL, LDR, BOPO, NIM, and CASA on ROA in PT. Bank Sumut.